Online assessment strategies to enhance students’ competence and their implementational challenges - Widiastuti, Ida Ayu Made Sri; Mantra, Ida Bagus Nyoman; Sukoco, Heru; Santosa, Made Hery (Universitas Muhammadiyah Sidoarjo, 2021)
Carrying out effective learning and appropriate classroom assessment during the coronavirus pandemic could be highly challenging for the teachers to do. Teachers need to utilize various technological devices to assess students' learning competence. This is due to online learning has become a priority in learning activities in the pandemic situation. This study found that English teachers implemented three types of online assessment strategies to improve students' learning competence during the pandemic of Covid-19 in Indonesia. Those strategies are online test administration, portfolio, and self-assessment. Several challenges were accoutered by the teachers in carrying out the classroom assessment through online systems such as slow internet network, expensive internet quota prices, limited access to computer and smartphone devices, poor ability in using digital technology, difficulty in conducting effective interaction. Feedback was occasionally provided when the learning processes were conducted through zoom meeting or google meet. The study implies that teachers should improve their communication technology ability and fulfill online assessment strategies' administrative procedures. HIGHLIGTS: Most teachers explain that they encountered similar challenges which were mainly about slow internet connection, expensive internet quota prices, poor ability in technology, and difficulty in communicating effectively with their students. The challenges encountered by the teachers were similar in their forms but the degree of difficulty depended upon the geographical location, economical background, and experiences in using technology Another difficulty encountered by teachers is providing feedback on the students’ assessment results. Teachers found it difficult to communicate directly to students to explain students’ problems in learning.